EPIC-Oxford: lifestyle characteristics and nutrient intakes in a cohort of 33 883 meat-eaters and 31 546 non meat-eaters in the UK. - Davey, G; Spencer, E; Appleby, P; Allen, N; Knox, K; Key, T (2003)
OBJECTIVE: To describe the lifestyle characteristics and nutrient intakes of the Oxford cohort of the European Prospective Investigation into Cancer and Nutrition (EPIC). DESIGN: Cohort of men and women recruited through general practices or by post to include a high proportion of non meat-eaters. Dietary, anthropometric and lifestyle data were collected at baseline and four diet groups were defined. SETTING: United Kingdom. PARTICIPANTS: In total, 65 429 men and women aged 20 to 97 years, comprising 33 883 meat-eaters, 10 110 fish-eaters, 18 840 lacto-ovo vegetarians and 2596 vegans. RESULTS: Nutrient intakes and lifestyle factors differed across the diet groups, with striking differences between meat-eaters and vegans, and fish-eaters and vegetarians usually having intermediate values. Mean fat intake in each diet group was below the UK dietary reference value of 33% of total energy intake. The mean intake of saturated fatty acids in vegans was approximately 5% of energy, less than half the mean intake among meat-eaters (10-11%). Vegans had the highest intakes of fibre, vitamin B1, folate, vitamin C, vitamin E, magnesium and iron, and the lowest intakes of retinol, vitamin B12, vitamin D, calcium and zinc. CONCLUSIONS: The EPIC-Oxford cohort includes 31 546 non meat-eaters and is one of the largest studies of vegetarians in the world. The average nutrient intakes in the whole cohort are close to those currently recommended for good health. Comparisons of the diet groups show wide ranges in the intakes of major nutrients such as saturated fat and dietary fibre. Such variation should increase the ability of the study to detect associations of diet with major cancers and causes of death.